Research on Multi-Function Pipeline Integrate Cloud Computing Monitoring System Based on OpenStack Structure - Lei Li; Lianwen Jin; Desheng Li; Wanwan Tang (Dianxin kexue)
To deal with the increasing of computer clusters which the increasing needs of cloud computing brings and guarantee stability and reliability of the service, a cloud computing monitoring system based on OpenStack structure to satisfy the needs of cloud computing monitor was designed. The system structure and key technologies were described, including factory model, Paste Deploy, pipeline, Eventlent green thread and object-oriented SQL Alchemy model, so the system has modularity, layering and pipeline. The advantage of the system includes multi-function integrating, easy deploy, high expansibility and redeveloping easily. The experimental result proves that the system has high stability, accurate data acquisition and high integration with the third client, and it can implement cloud computing monitoring informatization more effectively.